2013
DOI: 10.1007/s00774-013-0465-6
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone structure analysis of the spine using clinical MDCT: can it predict vertebral bone strength?

Abstract: Recent technical improvements have made it possible to determine trabecular bone structure parameters of the spine using clinical multi-detector computed tomography (MDCT). Therefore, the purpose of this study was to analyze trabecular bone structure parameters obtained from clinical MDCT in relation to high resolution peripheral quantitative computed tomography (HR-pQCT) as a standard of reference and to investigate whether clinical MDCT can predict vertebral bone strength. Fourteen functional spinal segment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…Using a specific calibration phantom, these MDCT scans may also be used to predict bone strength equivalent to QCT and subsequently assess fracture risk omitting the need for separate density scans [21]. This would potentially reduce radiation exposure, healthcare cost, time and effort particularly for patients with cancer, who routinely undergo MDCT examinations for staging, as they are often at increased risk for developing treatment related osteoporosis [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Using a specific calibration phantom, these MDCT scans may also be used to predict bone strength equivalent to QCT and subsequently assess fracture risk omitting the need for separate density scans [21]. This would potentially reduce radiation exposure, healthcare cost, time and effort particularly for patients with cancer, who routinely undergo MDCT examinations for staging, as they are often at increased risk for developing treatment related osteoporosis [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large demographic affected and the current rates of aging in our population, osteoporosis is becoming a significant health problem. The diagnosis and treatment of osteoporosis creates a substantial financial burden [7]. Accurate prediction of osteoporotic fracture risk can be of significant clinical benefit when assessing and managing osteoporosis.…”
Section: Motivation/purposementioning
confidence: 99%
“…The image voxel intensities were converted from HU to BMD units using the following equation as previously outlined in [7]: italicBMD=HAEHAAHUEHUAfalse(HUvoxelHUAfalse)…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…High-resolution trabecular bone imaging yields additional information beyond the areal BMD measurements obtained from DXA to predict bone strength [11], whereas HR-pQCT is limited to peripheral skeletal sites. On the other hand, although three reports have described microarchitectural analyses of wholebody CT obtained with conventional-resolution CT (CRCT) [12][13][14], no additional studies have suggested that the resolution of CRCT is critical for microarchitecture analysis. Two previous reports have described the relationship between microarchitectural parameters and spatial resolution using different CT scanners.…”
Section: Introductionmentioning
confidence: 99%